Selected Biological Medicinal Products and Their Veterinary Use - Zygmuntowicz, Aleksandra (Animals (Basel), 2020)
SIMPLE SUMMARY: Biological drugs are a generation of drugs that have developed thanks to advances in genetic engineering and molecular biology. Biological drugs are proteins derived from living cells or obtained through the use of genetic engineering methods with a selective and specific mechanism of action. Currently, these drugs are widely used in the treatment of many human diseases, but an increasing number of drugs from this group are also being used in the treatment of animals, mainly in dermatology, rheumatology and oncology. ABSTRACT: Definitions of biological medicinal products (BMPs) vary depending on the source. BMPs are manufactured using complex biological/biotechnological processes involving living cell lines, tissues and organisms such as microorganisms, plants, humans and even animals. Advances in modern biotechnological methods and genetic engineering have made it possible to search for new drugs with a targeted effect and simultaneous reduction of adverse effects, which has resulted in BMPs dynamically increasing their share in the pharmaceutical market. Currently, these drugs are widely used in the treatment of many human diseases, but an increasing number of drugs of this group are also being used in the treatment of animals, mainly in dermatology, rheumatology and oncology. This article presents the current state of knowledge in the field of biological medicinal products used in animal therapy.